Investigation of wire arc additive manufacturing of cylindrical components by using cold metal transfer arc welding process - K. Shunmugesh; Snobin Mathew; Arun Raphel; Raman Kumar; T. Ramachandran; Ashish Goyal; Abhijit Bhowmik (Scientific Reports)
Abstract This study investigates the use of Wire Arc Additive Manufacturing (WAAM) with the Cold Metal Transfer (CMT) process to fabricate high-quality cylindrical components from ER308L stainless steel. The primary objectives are to assess the mechanical properties—such as tensile strength, impact resistance, and hardness—while also exploring the metallurgical characteristics, including microstructure and grain size across different sections of the components. A detailed microstructural analysis reveals the uniformity and integrity of the components, with findings indicating a clear link between microstructural features and mechanical performance. Advanced characterization techniques, including optical microscopy and scanning electron microscopy, are employed to study the microstructure and failure mechanisms of the samples. The WAAM-CMT method produces components with high density and minimal defects, making them well-suited for a range of industrial applications, including cylindrical shells or housings in the marine and defense sectors, pressure vessels, and heat exchangers that require corrosion-resistant, high-strength materials. Additionally, the research highlights the cost-effectiveness and time-efficiency of WAAM, positioning it as a practical alternative for large-scale manufacturing in response to the growing demand for innovative production techniques. Overall, this study provides valuable insights into the potential of WAAM to address challenges in modern industry and contributes to advancing additive manufacturing technologies.